The Effect of Elixir of the Ethanol Extract of Rosa damascena on the Solubility of Urine Struvite Crystal in Wistar Rats - Kistia; Ginting, Chrismis Novalinda; Chiuman, Linda; Ginting, Sahna Ferdinand (European Journal of Applied Sciences, 2022)
Kidney stones are hard and solid masses formed by crystals in the urinary tract. Hence it should be treated appropriately. The use of Rosa damascena might be an option to help the recovery of the kidney and urinary tract. This study aims to show the potential of the elixir of the ethanol extract of Rosa damascena on the solubility of urine struvite crystal in Wistar rats. The experimental rats were divided into six groups: the control group (K0); magnesium oxide as an inducer (K-); inducer and Batugin elixir (K+); inducer and the elixir of the ethanol extract of Rosa damascena 250 mg/kg body weight (P1); 500 mg/kg body weight (P2) and 1000 mg/kg body weight (P3). The treatment was carried out for 28 days by examining urine crystals; urine pH was carried out on days 14 and 28, rat body weight measurements were carried out on days 14 and 28. At the end of the treatment period, the rats were necropsied using a combination of ketamine xylazine, and their kidneys were taken. Observations were made on the ratio of kidney of rats (w/w) and measurements of blood serum creatinine and urea levels using a spectrophotometer. The elixir of Rosa Damascena’s ethanolic extract demonstrated the potential of extract administration by raising weight gain, diminishing kidney weight ratio, reducing creatinine and blood urea concentrations, and lowering the number of kidney crystal deposits. The elixir of the ethanol extract of Rosa damascena has shown its potential to dissolve struvite crystals with the best dose of 250 mg/kg BW based on the number of urine crystals.